The efficiency-frontier approach for health economic evaluation versus cost-effectiveness thresholds and internal reference pricing: combining the best of both worlds?. (3rd September 2018) - Sandmann, Frank G.; Mostardt, Sarah; Lhachimi, Stefan K.; Gerber-Grote, Andreas
ABSTRACT: Introduction : The efficiency-frontier approach (EFA) to health economic evaluation aims to benchmark the relative efficiency of new drugs with the incremental cost-effectiveness ratios (ICERs) of non-dominated comparators. By explicitly considering any differences in health outcomes and costs, it enhances the internal reference pricing (IRP) policy that was officially endorsed by Germany as the first country worldwide in 1989. However, the EFA has been repeatedly criticized since its official endorsement in 2009. Areas covered : This perspective aims to stimulate the debate by discussing whether the main objections to the EFA are technically valid, irrespective of national contextual factors in Germany with reservations towards using cost-per-quality-adjusted life year (QALY) thresholds. Moreover, we comparatively assessed whether the objections are truly unique to the EFA or apply equally to IRP and cost-effectiveness thresholds. Expert commentary : The plethora of objections to the EFA (n = 20) has obscured that many objections are neither technically valid nor unique to the EFA. Compared with cost-effectiveness thresholds, only two objections apply uniquely to the EFA and concern intended key properties: (1) no external thresholds are needed and (2) the EFA is sensitive to price changes of comparators. Combining these policies and developing them further are under-utilized research areas.